2019
DOI: 10.1007/s00449-019-02242-2
|View full text |Cite
|
Sign up to set email alerts
|

Applications of off-gas mass spectrometry in fed-batch mammalian cell culture

Abstract: Off-gas analysis using a magnetic sector mass spectrometer was performed in mammalian cell cultures in the fed-batch mode at the 5 L bench and 50 L pilot scales. Factors affecting the MS gas traces were identified during the duration of the fed-batch cultures. Correlation between viable cell concentration (VCC) and oxygen concentration of the inlet gas into the bioreactor (O 2-in) resulted in R 2 ≈ 0.9; O 2-in could be used as a proxy for VCC. Oxygen mass transfer (kLa) was also quantified throughout the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The respiratory quotient (RQ), defined as carbon dioxide evolution rate (CER)/oxygen uptake rate (OUR), was also estimated and a distinct correlation between RQ and the metabolic state of the cell culture was established; when a cell culture was determined to be in the lactate production phase, the average RQ was above 1. Conversely, when the culture was determined to be in a lactate consumption phase, the average RQ was below 1 [94,95].…”
Section: Mass Spectrometry Techniquesmentioning
confidence: 95%
See 2 more Smart Citations
“…The respiratory quotient (RQ), defined as carbon dioxide evolution rate (CER)/oxygen uptake rate (OUR), was also estimated and a distinct correlation between RQ and the metabolic state of the cell culture was established; when a cell culture was determined to be in the lactate production phase, the average RQ was above 1. Conversely, when the culture was determined to be in a lactate consumption phase, the average RQ was below 1 [94,95].…”
Section: Mass Spectrometry Techniquesmentioning
confidence: 95%
“…Correlation between viable cell concentration and oxygen concentration of the inlet gas into the bioreactor was high, irrespective of scale for a CHO-GS cell line that expressed chimeric IgG4 monoclonal antibodies [94]. Additionally, the oxygen mass transfer coefficient (k L a) could also be identified throughout the culture with the mass spectrometer, and an impact of antifoam on k L a was found [94]. The respiratory quotient (RQ), defined as carbon dioxide evolution rate (CER)/oxygen uptake rate (OUR), was also estimated and a distinct correlation between RQ and the metabolic state of the cell culture was established; when a cell culture was determined to be in the lactate production phase, the average RQ was above 1.…”
Section: Mass Spectrometry Techniquesmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the past several years, numerous spectroscopic methods (e.g., Raman, near-infrared [NIR], fluorescence), capacitance sensors, turbidity measurements as well as advanced off-gas analysis have been adopted as PAT in biopharmaceutical manufacturing to monitor and control process performance (Goh et al, 2020;Kroll et al, 2017;Moore et al, 2019;Santos et al, 2018). These methods provide substantial information about multiple process and metabolite variables, while being non-invasive and non-destructive, hence representing excellent candidates for analysis of cell culture processes.…”
Section: Upstreammentioning
confidence: 99%
“…The in-situ combi-sensor was shown to be capable of determining qOUR together with turbidity measurement for the estimation of cell concentration for various hosts (Dahlmann et al, 2020). Another study showed that off-gas analysis using a magnetic sector mass spectrometer delivered reliable values for specific oxygen uptake rates for both bench and pilot scale cultivations (Goh et al, 2020). Furthermore, the authors correlated the respiratory quotient (RQ) to the metabolic state and viable cell density and differed between lactate production (average RQ > 1) and consumption phase (average RQ < 1).…”
Section: Upstreammentioning
confidence: 99%